2022
DOI: 10.1159/000522499
|View full text |Cite
|
Sign up to set email alerts
|

Time Spent Away from Bed to Maintain Swallowing Function in Older Adults

Abstract: <b><i>Introduction:</i></b> The aim of this study was to determine the associations of time spent away from bed with whole-body muscle mass and swallowing function in older adults with low activities of daily living (ADL). <b><i>Methods:</i></b> This cross-sectional study was conducted at Tokyo Medical and Dental University and included adults over 65 years of age who underwent a medical intervention at their residence. Data regarding age, sex, body height and we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Considering this, physical activity intervention may be an effective approach for improving intramuscular adipose tissue in the quadriceps in older inpatients with aspiration pneumonia. Ishii et al [ 50 ] targeted older patients with low ADL and reported that the swallowing ability in older patients who spent 4 or more hours away from the bed in a day was higher than that of older patients who spent less than 4 hours away from the bed. The results of this study indicate that there is a relationship between physical activity and swallowing ability, and thus, support our hypothesis (intervention with physical activity for decreasing intramuscular adipose tissue of the quadriceps is needed to improve swallowing ability in older patients with aspiration pneumonia).…”
Section: Discussionmentioning
confidence: 99%
“…Considering this, physical activity intervention may be an effective approach for improving intramuscular adipose tissue in the quadriceps in older inpatients with aspiration pneumonia. Ishii et al [ 50 ] targeted older patients with low ADL and reported that the swallowing ability in older patients who spent 4 or more hours away from the bed in a day was higher than that of older patients who spent less than 4 hours away from the bed. The results of this study indicate that there is a relationship between physical activity and swallowing ability, and thus, support our hypothesis (intervention with physical activity for decreasing intramuscular adipose tissue of the quadriceps is needed to improve swallowing ability in older patients with aspiration pneumonia).…”
Section: Discussionmentioning
confidence: 99%
“…For patients who do not prefer community or common dining, chairs and tables in the rooms can be used. Over-the-bed tables promote time in bed and increase risk of aspiration, so should not be a part of geriatric hospitals ( Manganelli et al., 2014 ; Ishii et al, 2022 ).…”
Section: Geriatric Hospitals: Changing Typical Processes Of Care and ...mentioning
confidence: 99%
“…Crosssectional studies have found that healthy adults who are more physically active have higher tongue strength and longer endurance, with the association more obvious in older adults (VanRavenhorst-Bell et al, 2017). Focusing on older adults, those who were more active in daily life have shown better performance in oromotor (Izuno et al, 2016;Morishita et al, 2021) and swallowing measurements (Ishii et al, 2022(Ishii et al, , 2023Morishita et al, 2021). The mode of physical activity may also make a difference, with adults who are weight lifters showing higher tongue strength and runners showing longer tongue endurance (VanRavenhorst-Bell et al, 2018); this suggests that there may be a difference between the transfer of aerobic and anaerobic WBE effects to non-targeted muscles.…”
Section: Introductionmentioning
confidence: 99%